Asian Aproaches and The Theology of Karl Rahner - Lawrence Ng Yew Kim (P3TK, Sanata Dharma University, 2019)
This article explores how Rahners work can fit within an Asian theological approach of understanding God. For many Asians, religion is a lived experience and being a Christian is a choice that can be counter-cultural. Christianity is still commonly perceived as a Western religion in many parts of Asia. This may result in a re-thinking of what it means to be an Asian Christian beyond the Western context. This article will offer some thoughts on the Asian approach to theology and then consider aspects of Rahners thought that can appeal to Asian sensibilities. Though Rahner comes from a Western context, there is a commonality in his work, which can speak to the Asian lived faith experience and their orientation towards the divine.